Fine-needle aspiration cytology of metastatic squamous cell carcinoma thyroid: A rare entity - Kundu, Reetu (J Cytol, 2014)
Metastasis to the thyroid gland is rare with majority of cases discovered during an autopsy. Clinical presentation with a palpable thyroid or functional disturbances in thyroid is uncommon. We report isolated metastasis of laryngeal squamous cell carcinoma (SCC) to the thyroid gland diagnosed on fine-needle aspiration cytology which is minimally invasive and a preferred preliminary diagnostic modality in palpable thyroid swellings. A diagnosis of extra thyroidal SCC is a diagnosis of exclusion when there is no evidence of a coexistent recognizable primary thyroid cancer and/or molecular signatures suggestive of thyroidal origin.